(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2025)
The teaching of dictatorial pasts in recent history represents a key challenge for educational systems in Latin America. This study systematically reviews curricula, textbooks, and teaching practices in Chile, Argentina, Uruguay, and Brazil, following PRISMA standards. After analyzing indexed publications from the past six years, 71 empirical documents were selected. The findings reveal controversial curricular approaches that tend to naturalize historical processes and overlook social conflicts. This underscores the need to adopt critical perspectives that foster reflective and analytical memory rather than commemorative approaches. The conclusions highlight the importance of dialogical and critical teaching methods aimed at strengthening civic education and building a historical memory committed to democratic values.